Effect of varying resin content and board densities on the properties of three layers particleboard from kelempayan / Tuan Mohd Fakrul Razie Tuan Ismail and Nurrohana Ahmad - Tuan Ismail, Tuan Mohd Fakrul Razie; Ahmad, Nurrohana (2015)
The aim of this study was to investigate the use of Kelempayan species in manufacturing three layer particleboard panels. The boards were fabricated with three different densities (500 kg/m3, 600 kg/m3 and 700 kg/m3). The sample also has different level of the resin content (8 %,10 % and 12 %). The boards produced were evaluated for its' modulus of rupture (MOR), modulus of elasticity (MOE), internal bond (IB), water absorption (WA) and thickness swelling (TS) in accordance with the Japan industry Standards (JIS) A 5908:2003. The result meet requirement and passed standard value based on JIS A 5908:2003 Type 13 for mechanical properties is board at density 600 kg/m3 with resin 12 %, the result shown in MOR (14.94 MPa) and IB (0.29 MPa). For density 700 kg/m3 with resin 8% and 10 % only MOR and IB passed the standard. At the same density for resin 12 %, the all mechanical properties passed the standard value of JIS. For physical properties, only one parameter combination passed in thickness swelling (11.90 %), I.e. density 600 kg/m3 and 12 % resin content. It is concluded that the boards with density of 700 kg/m3 were able to fulfil the JIS requirements.